1991
DOI: 10.1017/s0022112091000241
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal jets and vortex dipoles in a stratified fluid

Abstract: When a horizontal force is applied locally to some volume of a viscous densitystratified fluid, flows with high concentration of vertically oriented vorticity (vortex dipoles) are generated. The processes of generation and evolution with time of these unsteady flows in a stratified fluid are studied. A convenient way to produce and study these flows in the laboratory is to use a submerged horizontal jet as a ‘point’ source of momentum. The main governing parameter (the ‘force’) is easily controlled in this cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(50 citation statements)
references
References 14 publications
3
47
0
Order By: Relevance
“…11. As can be seen, the flow k> development is qualitatively similar to the case of zero shear [22] with the resulting planar dipolar eddy. The main difference here is that the initial turbulent blob (Fig.…”
Section: Dipolar Eddies In a Shear Flowsupporting
confidence: 57%
“…11. As can be seen, the flow k> development is qualitatively similar to the case of zero shear [22] with the resulting planar dipolar eddy. The main difference here is that the initial turbulent blob (Fig.…”
Section: Dipolar Eddies In a Shear Flowsupporting
confidence: 57%
“…In many situations Re* and Fr* can be very large initially, but at the late stages of the flow development, with typical flow velocity and length scales U 0 and D 0 , the flow parameters, Re 0 ϭU 0 D 0 / and Fr 0 ϭU 0 /ND 0 , become small ͑because U 0 decreases and D 0 increases with time and U 0 usually decreases faster than D 0 increases͒ and so-called flow laminarization occurs with time. 12 At small Fr 0 stratification suppresses the vertical component of the velocity and the flow becomes quasi-twodimensional. Indeed, observations show that the far wake consists of long lasting patches of vertical vorticity of opposite signs ͑''pancake'' eddies͒ organized into a vortex street, the vertical length and velocity scales of which are much smaller than those in the horizontal direction.…”
Section: Introductionmentioning
confidence: 99%
“…Many laboratory experiments have shown that quasitwo-dimensional vortex dipoles are generically produced by the collapse of initially three-dimensional turbulent jetlike flows when submitted to specific constraints such as a density stratification (Voropayev et al 1991;Flór et al 1995) or a small fluid-layer thickness (Sous et al 2004;Voropayev et al 2007). In Voropayev et al (2007) and Sous et al (2004), an impulsive jet in a shallow layer of water is used to mimic the aforementioned geophysical flow configurations.…”
Section: Introductionmentioning
confidence: 99%